NS3 protease polymorphisms and genetic barrier to drug resistance of distinct hepatitis C virus genotypes from worldwide treatment-naïve subjects - Vidal, L. L.; Soares, M. A.; Santos, A. F. (Journal of viral hepatitis, 2016)
Summary Hepatitis C virus (HCV) NS3 protease inhibitors have been primarily designed against genotype 1, the one with the lowest response to dual therapy. However, less evidence of their efficacy on non‐1 genotypes is available, and any such information is mostly concentrated on genotypes 2‐4. This study evaluated HCV protease resistance profiles in the major six HCV genotypes and identified genetic barrier (GB) profiles to each available protease inhibitor across HCV strains from different locations worldwide. We obtained 15 099 HCV sequences from treatment‐naïve subjects retrieved at the Los Alamos HCV Sequence Database. The wild‐type codons of different HCV genotypes were used to analyse the smallest number of nucleotide substitution steps required for changing that codon to the closest one associated with drug resistance. The 36L and 175L RAVs were found as genetic signatures of genotypes 2‐5, while the 80K RAV was found in all genotype 5 sequences. Genotypes 4 and 6 showed a higher GB to RAV mutations conferring resistance to telaprevir, while genotypes 2‐5 presented baseline resistance to that drug, carrying the 36L mutation. Genotype 4 had a higher GB to simeprevir resistance, requiring three substitutions to acquire the 155K mutation. Subtype 1b showed a higher GB than subtype 1a to resistance for most PIs, with RAVs at codons 36 and 155. Geographic disparities were also found in frequencies of certain RAVs in genotypes 2 and 3. Under a scenario of unprecedented evolution of anti‐HCV direct‐acting agents, the genetic composition of the circulating HCV sequences should be evaluated worldwide to choose the most appropriate/feasible therapeutic schemes with the highest genetic barriers to resistance.